Thinking sensibly about recovery - Sands, W. A. (Strength and conditioning for sports performance, 2016)
`Recovery` is an enigma. The area of `recovery` seems to have become an idea worth exploring and exploiting, perhaps through necessity or a lack of imagination following the loss of the obvious benefits of now-illegal drugs. Many recovery-based ideas are being recycled with modification and offered to those hungry for a competitive edge anywhere they can find it. There is a paucity of direct evidence-based information on recovery, along with many serious definitional problems. There is no consensus on terms, assumptions and cause—effect linkages. I believe it is important to understand where our thinking about recovery can be wrong-headed and how we might avoid twisting observations to fit our preconceptions. Robson-Ansley and colleagues wrote about fatigue management and recovery following the 2008 Beijing Olympic Games. After studying the practical use of numerous recovery methods and modalities, `We conclude that well-accepted methods such as sufficient nutrition, hydration, and rest appear to be the most effective strategies for optimizing recovery in Olympic athletes` [143, p. 1409], Contemplating recovery approaches requires a journey of understanding that is fraught with definitional problems, the lack of a conceptual framework, and untested assumptions. Before exploring recovery, let us understand training.